2020
DOI: 10.1111/ijlh.13167
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA Lnc‐IRF2‐3 and Lnc‐ZNF667‐AS1 is associated with poor survival in B‐chronic lymphocytic leukemia

Abstract: Background Lnc‐IRF2‐3 and Lnc‐ZNF667‐AS1 were recently studied as a positive biomarker for many tumor cells. However, experimental studies found that they are associated with worse outcomes in B‐CLL. Methods A prospective case study was conducted on 135 B‐CLL patients that were compared to thirty healthy controls. The patients were followed up for 40 months and quantitative measurements of Lnc‐IRF2‐3 and Lnc‐ZNF667‐AS1 were measured and compared between the two groups as well as high‐risk and low low‐risk B‐CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Several publications have already highlighted the differential patterns on transcriptomics and epigenomics layers ( 8 , 19 , 33–35 ) in these disease subgroups, hence suggesting the biological relevance of InterTADs. Focusing on the IG SHM status, we found genes that were targeted by more than one event, such as KCNJ2 ( 51 ) , CRY1 ( 51 ) , ZNF667-AS1 ( 52 ) , MYLK ( 51 ) , ZAP70 ( 53 ), all of which have been previously identified in previous reports. We also observed that events of inactive regions in U-CLL were enriched for binding sites of several TFs relevant to B cell/CLL biology, while also showing differential expression between the two groups, including the ATF5 ( 54 ), MYBL2 ( 55 ).…”
Section: Discussionsupporting
confidence: 57%
“…Several publications have already highlighted the differential patterns on transcriptomics and epigenomics layers ( 8 , 19 , 33–35 ) in these disease subgroups, hence suggesting the biological relevance of InterTADs. Focusing on the IG SHM status, we found genes that were targeted by more than one event, such as KCNJ2 ( 51 ) , CRY1 ( 51 ) , ZNF667-AS1 ( 52 ) , MYLK ( 51 ) , ZAP70 ( 53 ), all of which have been previously identified in previous reports. We also observed that events of inactive regions in U-CLL were enriched for binding sites of several TFs relevant to B cell/CLL biology, while also showing differential expression between the two groups, including the ATF5 ( 54 ), MYBL2 ( 55 ).…”
Section: Discussionsupporting
confidence: 57%
“… 18 Moreover, Lnc-IRF2-3 and Lnc-ZNF667-AS1 owned high specificity and sensitivity to distinguish B-chronic lymphocytic leukemia (B-CLL) between healthy controls and were potential prognostic indicators in B-CLL. 19 For RCC, quite a few lncRNAs have been identified to have involvement in diagnosis or prognosis. 20 Ellinger et al quantified the lnc-ZNF180-2 expression in patients with ccRCC and concluded it may be a useful prediction factor of ccRCC patients’ outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, the highest levels of Lnc-IRF2-3 and Lnc-ZNF667-AS1 were found in CLL patients with del17p and del11q, respectively. Of note, increased expression of these lncRNAs was associated with poor prognostic factors, including high levels of ZAP70 protein and un-mutant IGHV [ 113 ]. In contrast, lncRNA is associated with ZAP70 protein levels and un-mutant IGHV.…”
Section: Alterations In Lncrnas In Lymphoid Malignancymentioning
confidence: 99%